2024
DOI: 10.3991/ijim.v18i01.46307
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology in Education: Opportunities, Challenges, and Beyond

Agariadne Dwinggo Samala,
David Mhlanga,
Ljubisa Bojic
et al.

Abstract: Blockchain technology has gained significant attention for its decentralized, secure, transparent, and immutable characteristics. It has been adopted in various domains, including the financial and education sectors. This systematic review provides a comprehensive analysis of the opportunities, challenges, and future educational prospects of blockchain technology by examining published research from various disciplines. A bibliometric approach was adopted using R Studio. Datasets were sourced from the Scopus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, classrooms and labs equipped with IoT sensors to monitor and enhance the educational environment. Also, blockchain-based systems (Samala et al, 2024) and educational robots (Schiavo et al, 2024), that are becoming increasingly popular in education, will be used to enhance learning experiences and develop essential skills in students at the university of the future.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, classrooms and labs equipped with IoT sensors to monitor and enhance the educational environment. Also, blockchain-based systems (Samala et al, 2024) and educational robots (Schiavo et al, 2024), that are becoming increasingly popular in education, will be used to enhance learning experiences and develop essential skills in students at the university of the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that AI-based technologies (Kamalov et al, 2023;George & Wooden, 2023), VR and AR, LMS, and cloud computing (Zhao et al, 2023) enhance the educational process significant. Other technological advancements are IoT (Razzaq et al, 2020), blockchain-based systems (Samala et al, 2024) and educational robots (Schiavo et al, 2024). In the context of studying of pedagogical innovations, we discovered that they primarily focus on creating more flexible educational process (Bizami et al, 2023).…”
Section: Project-based Learningmentioning
confidence: 99%
“…However, challenges such as regulatory compliance, interoperability, and user adoption must be addressed to fully harness the potential of blockchain in higher education. The authors [20] highlight the potential of BT to revolutionize the education sector while emphasizing the need to address privacy concerns. Another approach by the authors [21] is to verify micro-credentials, emphasizing the necessity of a reliable and secure strategy for leveraging blockchain technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implementation of health information systems, advanced medical devices, and the utilization of health mobile applications provides efficient support in the diagnosis, treatment, and management of health. These innovations not Aulia Asman 1 , Yulkifli 2 , Yohandri 2 , Naurah Nazhifah 2 , Soha Rawas 3 , Agariadne Dwinggo Samala 4 () only enhance the quality of healthcare services but also offer improved monitoring capabilities for patients' conditions [5], [6].…”
Section: Introductionmentioning
confidence: 99%